OPTIMIZATION OF ANAEROBIC TREATMENT OF CASSAVA PROCESSING WASTEWATER - Fleck,Leandro (2017)
ABSTRACT The main contribution of this research is to optimize the operating conditions of an anaerobic reactor applied to the treatment of wastewater from cassava starch production. A 20-L anaerobic reactor was used, operating in a batch system, with temperature control. Temperature and inoculum total volatile solids (TVSi) were controlled for evaluation of effects on the removals of chemical oxygen demand (COD) and reactor total volatile solids (TVSr) by means of a Central Composite Rotational Design (CCRD). Twelve trials were analyzed simultaneously by the desirable function approach. The higher COD removal (96.82%) was obtained at 42 °C and 12.0% TVSi. The largest TVSr removal (69.31%) was registered at 45 °C and 10.0% TVSi. Equations representative of the process were obtained from the responses of variables, being statistically significant at a 90% confidence level. Based on the desirability function approach, we can conclude that an optimal operational condition for the anaerobic reactor is at 39.7 °C and 10.8% TVSi. The estimated COD and TVSr removal efficiencies under these operating conditions were 90.45% and 63.12%, respectively.